Faktor–Faktor Yang Berhubungan dengan Perilaku Merokok di Dalam Rumah - Rarasati, Diah; Putri, Riska Hediya; Qurniasih, Nila; Kristianingsih, Ani (Wellness And Healthy Magazine, 2021)
Lung cancer ranks on the first as the cause of death, which is 12.6% (Globocan, 2018). The genesis of lung cancer in Indonesia is based on data from the Friendship Center General Hospital, 87% of lung cancer cases are caused by smoking behavior, both passive and active smokers. The number of smokers in Indonesia is still high, the number of passive smokers is 78.4% or 133.3 million adults exposed to cigarette smoke in their homes. Passive smokers can be attacked by various diseases such as lung cancer and respiratory diseases because cigarette smoke contains more than 4000 chemicals. In addition, if it is associated with maternal and child health, smoking can cause ARI disease that attacks the human respiratory tract with the number of infected children mostly in children. The research objective was to determine the correlate factors to the smoking behavior in the home at Pekon Sukadamai of Gunung Alip Sub-District in Tanggamus Regency. This type of research is a quantitative research with a cross sectional study design. The population in this research were all households with infants and toddlers in Sukadamai Village, amounting to 63 families. The sample in this research amounted to 63 respondents. Sampling in this research used a total sampling technique. The analysis used the chi square test. The results of the research showed that there was no correlation between knowledge (p value 0.90) and attitude (p value 0.07) with smoking behavior in the home at Pekon Sukadamai of Gunung Alip sub-district in Tanggamus Regency (p value = 0.000). Suggestions for the community are expected to be more diligent in adding insight by following the counseling provided by the public health center.